2001
DOI: 10.1148/radiol.2211001499
|View full text |Cite
|
Sign up to set email alerts
|

Relative Attractiveness of Diagnostic Radiology: Assessment with Data from the National Residency Matching Program and Comparison with the Strength of the Job Market

Abstract: Medical students appear to have an in-depth understanding of the economic forces at play in the health care job market and incorporate this information into their choice of a specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] These factors range across a wide spectrum from individual characteristics such as personality 1 to anticipation of specialtyrelated income. [2][3][4][5][6] Recently, specialtyrelated lifestyle has drawn increased attention as US medical students have applied in increasing numbers to radiology [9][10][11] and anesthesiology 9,10 programs and in decreasing numbers to general surgery and family practice programs. 9,10,12,13 Studies have suggested that a so-called controllable lifestyle has become a determinant in students' specialty selection criteria.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] These factors range across a wide spectrum from individual characteristics such as personality 1 to anticipation of specialtyrelated income. [2][3][4][5][6] Recently, specialtyrelated lifestyle has drawn increased attention as US medical students have applied in increasing numbers to radiology [9][10][11] and anesthesiology 9,10 programs and in decreasing numbers to general surgery and family practice programs. 9,10,12,13 Studies have suggested that a so-called controllable lifestyle has become a determinant in students' specialty selection criteria.…”
mentioning
confidence: 99%
“…The reason for this is speculative. Some suggest that diagnostic radiology itself is an attractive specialty, 18 therefore trainees are less inclined to pursue IR. Conversely, others argue that the majority of students do not consider radiology as a career choice due to its lack of patient contact.…”
Section: Increasing Awareness Of Ir By Reforming the Undergraduate Cumentioning
confidence: 99%
“…Others [21][22][23] have argued that beliefs about various professions are deeply engrained and difficult to change, and that radiology is perceived as having regular hours and a healthy lifestyle, both of which may influence career choices more heavily than whether a dedicated radiology curriculum is offered. Thus, radiology education certainly may have an impact on career choice, but that effect may be muted by other motivators such as future job prospects and lifestyle [24].…”
Section: Discussionmentioning
confidence: 99%